Design of a transonic airfoil - Lim, Jing Kai. (2011)
This project will investigate the actuation forces and energies required to change the camber of a transonic morphing airfoil. Current studies on variable-camber morphing airfoils primarily concern themselves with computational analyses and models of the actuation forces and energies required for morphing, with few studies delving into the area of the actual construction of a morphing airfoil nor the measurement of the predicted quantities. The use of variable-camber morphing airfoils in the design of transonic airfoils is beneficial as transonic airfoils typically have poorer aerodynamic performance at low speeds due to their small camber. On the other hand, subsonic airfoils optimized for low Reynolds numbers exhibit high wave drag in the transonic regime. A morphing airfoil which is able to change its profile to optimize its performance in both the subsonic and transonic speed regimes would provide performance benefits to aircraft operating in these 2 regimes.